Morphologic changes of the incisive canal and its proximity to maxillary incisor roots after anterior tooth movement - Yu, Ji Hee; Nguyen, Tung; Kim, Yong-Il; Hwang, Soonshin; Kim, Kyung-Ho; Chung, Chooryung J. (American journal of orthodontics and dentofacial orthopedics, 2022)
The objectives were to evaluate the morphologic changes of the incisive canal (IC) and the influence of IC proximity to apical root resorption of maxillary central incisors after anterior tooth movement. Pretreatment and posttreatment cone-beam computed tomography images of adults (aged 18-47 years) were retrospectively evaluated. Subjects were divided into control group with minimal incisor movement (n = 32; maxillary incisor tip movement <2 mm) and maximum retraction group (n = 35; maxillary incisor tip movement >4 mm). The shape, direction, morphologic changes of the IC, the proximity of the central incisor root to IC, and the amount of apical root resorption associated with the proximity after orthodontic treatment were compared. Changes in the shape of the IC were not observed in both control and retraction groups. However, 11.4% (4 of 35 subjects) in the retraction group indicated changes in the direction of the IC from slanted-straight to slanted-curved type after the direction of anterior retraction. The thickness of the cortical bone surrounding the IC and the distance between the incisor root and IC significantly decreased after orthodontic treatment in both groups (P <0.05). However, these changes were significantly greater in the retraction group than in control (P <0.0001). Contact or invasion of the incisor root to the IC was more prominent in the retraction group (42.8%-54.3%) than the control (10.9%-12.5%) (P <0.0001). The amount of root resorption indicated a tendency to increase in the order of separation, approximation, contact, and invasion in relation to IC. Although remodeling of IC was evident in some patients, contact or invasion of the maxillary central incisor roots to IC was fairly high after maximum anterior retraction. •Posttreatment morphologic changes of the incisive canal (IC) and root proximity were evaluated.•Four of 35 patients (11.4%) showed remodeling changes in IC direction after anterior retraction.•Changes in the thickness of the cortical bone surrounding the IC and root approximation were seen.•Contact of the incisor root to IC was higher after maximum anterior retraction.•The minor incisal movement produced less contact.